Challenging cognitivism: computational versus embodied and embedded creativity in AI generative music - Garcia, Matheus P. (Anais do Simpósio Brasileiro de Computação Musical, 2025)
This paper aims to discuss different perspectives on the nature of cognition in relation to artificial intelligence as a tool for artistic creativity. We bring forth the debate between two important lines of thought in cognitive science: first, we present a brief overview of the computational and representational theory of mind, which posits that the mind functions similarly to a computer, gathering information through the sensory organs and processing this information by means of an internal, symbolic language. We argue that this cognitive point of view is closely linked to the development of the first artificial neural networks and represents a dominant perspective in the field of artificial intelligence to this day. Then, we discuss the idea of embodied and extended cognition, which differs radically from the first by stating that the process of acquiring knowledge is carried out not solely by the brain, but by the entire organism, engaging in constant exchange with its environment through complex mutual modeling. From this debate, we explore the field of generative artificial intelligence by presenting artistic experiences and perspectives in AI-generated music that challenge the cognitivist notion that the brain and computer function in fundamentally similar ways.